Savi and the memory keeper - Vachharajani, Bijal (Gurugram Hachette, 2021)
This book is a fantastical and real, where tree hugs heal and wasps are saviours. The author skilfully weaves a narrative of personal and climate grief and the healing power of nature.
Keywords: Fiction